Bosnia and Herzegovina : Calculation of Cyclically Adjusted Budget Balance and Assessment of Fiscal Policy Stance - Hlivnjak, Sandra; Laco, Matija (World Bank, Washington, DC, 2018)
What is the real character of fiscal policy? Is it expansionary or restrictive? Is it pro-cyclical or does it have stabilization effects? Policymakers and economic analysts need to be able to ascertain fiscal policy effort. As the actual budget balances are affected both by cyclical factors and structural measures, they may not, in general, be very useful when seeking to assess the stance of the fiscal policy. To understand the true nature of fiscal policy, it is therefore fundamental to remove cyclical effects of general government budget balances. The cyclically-adjusted budget balance (CAB) indicator plays this role in the fiscal surveillance framework as a means of analyzing the fiscal situation and changes in policy that result from the intentional actions of the government. This paper, for the first time, provides detailed calculations of the cyclically-adjusted budget balances in BiH, following a commonly agreed method by the European Commission and assesses the character of the fiscal policy in BiH from 2008 to 2019. The analysis showed that in earlier years BiH had led stabilizing expansionary fiscal policy, while in more recent years the fiscal policy was mostly restrictive and procyclical